البطاقات الائتمانية في البنوك التشاركية وأثرها على الاقتصاد: البنوك التشاركية التركية أنموذجا - عويضة، عدنان عبدالله محمد; ابن مجشر، محمد يسلم مفتاح (مركز البحث وتطوير الموارد البشرية - رماح, 2023)
تلعب البطاقات الائتمانية دورا مهما في النشاط الاقتصادي عموما، وعلى وجه الخصوص في النشاط الاستهلاكي، حيث جعلت حياة الناس أكثر سهولة وأمانا بالحفاظ على أموالهم واستثمارها بطرق مختلفة، حيث تعد تركيا من الدول المبادرة على المستوى الأوروبي استخداما للبطاقات الائتمانية وقد تقدمت على بريطانيا نظرا للكتلة البشرية التي تتمتع بها، ومما لا شك فيه أن أثر البطاقات الائتمانية في الجمهورية التركية يعتمد على أداء القطاع المصرفي ككل وعلى أداء البنوك التشاركية بشكل خاص، كذلك يعتمد على مدى ثقة العملاء بالبنوك التشاركية وما يصدر عنها من خدمات مصرفية وصيغ تمويل. وقد خلصت الدراسة إلى أن البطاقات الائتمانية كان لها دور بارز في تنشيط القطاع التجاري، ولها دور إيجابي في الإسهام في نمو الاقتصاد التركي، حيث أظهرت البيانات المتاحة بأن البطاقات المصرفية في تركيا والتي تضاعفت أعدادها بواقع ثلاث بطاقات لكل مواطن في الأعوام الأخيرة، قد أثرت تأثيرا إيجابيا على النمو الاقتصادي حيث يتمتع الاقتصاد التركي بجهاز عرض مرن نسبيا، إلا أن هذا الأثر ترافق مع أثار تضخمية تفسر بتكلفة الطاقة المستوردة اللازمة للنمو الاقتصادي. وقد لعبت البطاقات الائتمانية دورا كبيرا في نمو الاقتصاد التركي بنسبة 35% حتى في ظل جائحة كوفيد-19. Credit cards play an important role in economic activity in general, and in particular in consumer activity, as they have made people’s lives easier and safer by preserving and investing their money in different ways, and bank cards are also likely to have a positive or negative impact on the national economy of the countries that deal with them,, As Turkey is one of the countries that initiates the use of credit cards at the European level and has advanced to Britain due to the human mass that it enjoys, and there is no doubt that the impact of credit cards in the Turkish Republic depends on the performance of the banking sector as a whole and on the performance of participatory banks in particular, as well as on The extent of customer confidence in participatory banks and the banking services and financing formulas issued by them. The study concluded that credit cards had a prominent role in revitalizing the commercial sector. They had a positive role in contributing to the growth of the Turkish economy, as available data showed that bank cards in Turkey, whose numbers have doubled by three cards per citizen in recent years, have affected A positive impact on economic growth, as the Turkish economy enjoys a relatively flexible supply system, but this effect was accompanied by inflationary effects that are explained by the cost of imported energy needed for economic growth. Credit cards have played a big role in the growth of the Turkish economy by 35%, even in light of the Covid-19 pandemic.
Keywords: المؤسسات المالية -- البطاقات المصرفية -- الاقتصاد الوطني -- النمو الاقتصادي -- تركيا